2023
DOI: 10.7759/cureus.36032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Filler Particle Sizes on the Physical Properties of Bulk-Fill Composites Compared to Conventional Composites

Abstract: Introduction: Filler size affects how the material is coated and finished, while filler stacking affects how strong the material is, how flexible it is, how resistant it is to wear, and how much it shrinks when it polymerizes. The purpose of this research was to compare micro-hybrid, nano-composite, and bulk-fill composites with respect to their compressive strength, diametric tensile strength, and flexural strength. Materials and methods: To organize the samples according to International Organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Few studies also reported that Epoxy polymer matrix provides good stiffness, high strength and good corrosion resistance 7,8 . The filler material, weight ratio of resin to fiber and the particle size of the fillers influence the mechanical performance of the polymer composites [9][10][11] . The performance of a material under the conditions of wear and friction between the mating parts also play a pivotal role in selecting them for tribological applications.…”
mentioning
confidence: 99%
“…Few studies also reported that Epoxy polymer matrix provides good stiffness, high strength and good corrosion resistance 7,8 . The filler material, weight ratio of resin to fiber and the particle size of the fillers influence the mechanical performance of the polymer composites [9][10][11] . The performance of a material under the conditions of wear and friction between the mating parts also play a pivotal role in selecting them for tribological applications.…”
mentioning
confidence: 99%